LITERATURE REVIEW : HUKUM LINGKUNGAN DARI PERSPEKTIF KEARIFAN LOKAL - Putra, Surya Eka; Frinaldi, Aldri (JURNAL BUANA, 2024)
This study aims to look at the relationship between environmental law and local wisdom and the impact arising from the existence of environmental law on local wisdom. The writing method used in this study is a qualitative method using relevant journal studies to strengthen the theory. This article reviews the relationship between environmental law and local wisdom and the impacts arising from the existence of environmental law on local wisdom. The results of this study can be concluded in this literature review article are: 1) The nature of the environment is determined by several factors. First, the types and each type of environmental elements. Second, the relationship or interaction between elements in the living environment. Third, the behavior or condition of the environmental elements. Fourth, non-material factors of temperature, light and noise. 2) The existing relationship between environmental law and local wisdom is the law that underlies the implementation of environmental protection and governance itself. 3) The existence of environmental law has an important role in overcoming various environmental damages that occur